SAT0670 The prevalence of neuropathic pain-like symptoms and associated risk factors in the nottingham community: a cross-sectional study. (15th June 2017) - Fernandes, GS; Sarmanova, A; Warner, S; Harvey, H; Richardson, H; Frowd, N; Marshall, L; Stocks, J; Hall, M; Valdes, A; Walsh, D; Zhang, W; et al.
Abstract : Background: Knee pain (KP) affects 1 in 4 adults over the age of 50. Aside from structural joint changes, person-specific factors influence the KP experience. Increased central sensitisation of neural pathways due to localised joint pain or ineffective descending inhibitory mechanisms can cause an enhanced pain response and neuropathic pain-like (NP) symptoms. Understanding these person-specific factors and how they modulate the pain experience might help profile different KP and NP phenotypes. Objectives: a) To determine the prevalence of NP in a KP community population b) to identify significant risk factors associated with NP and those with both NP and non-NP KP. Methods: 9, 513 men and women, aged 40+ years, were recruited from the East Midlands region (United Kingdom) via postal questionnaire. The questionnaire included sections on KP severity (numerical rating scale) and type (NP versus nociceptive) using the modified PainDETECT Questionnaire (mPDQ); quality of KP using the intermittent and constant osteoarthritis pain (ICOAP) instrument) as well as other risk factors including age, body mass index (BMI), injury, pain catastrophizing scale (PCS) and mental wellness (Hospital Anxiety and Depression Scale). KP participants were those who reported "knee pain for most days of the past one month" while likely NP was mPDQ scores of ≥13 and definite NP, ≥19. Differences between groups were assessed using t-tests for continuous data and chi 2 for categorical data. We used multinomial regression analysis to determine the odds ratios (ORs) of risk factors with 95% confidence intervals (CI) and significance set p <0.05. Results: The prevalence of definite NP in the Nottingham Community was 366 (13.62%). There were more women (p=0.04) and higher BMI (p<0.001) in KP vs. non-KP responders but no age difference (p>0.05). When comparing the neuropathic-like KP to non-neuropathic KP responders, significant risk factors after adjustment for age, BMI, gender and pain severity included: anxiety (OR 3.17 (95% CI 2.38;4.23)); depression (OR 2.99 (95% CI 2.14;4.19)); PCS in highest tertile (OR 5.39 (95% CI 2.94;9.88)); fibromyalgia (OR 4.06 (95% CI 2.48;6.66)) and previous knee injury (OR 1.5 (95% CI 1.12;2.00)). When comparing neuropathic-like KP to non-KP responders, anxiety (1.74 (95% CI 1.31; 2.30), depression (2.05 (95% CI 1.40; 3.01), PCS 3.78 (95% CI 2.57; 5.56)), fibromyalgia (OR 1.94 (95% CI 1.10; 3.40)) and previous injury (OR 1.35 (95% CI 1.05; 1.73)) were significant risk factors after adjustment. Conclusions: This is the first population based cross-sectional study in the UK to determine prevalence of NP in people with KP. The results suggest that both psychological factors (depression, anxiety, high catastrophising) and peripheral risk factors (injury) associate with NP reporting. These factors can augment pain sensitivity and produce an amplified response via central and peripheral pathways. Phenotypes based on these risk factor profiles may warrant specific management in KP populations. Acknowledgements: Arthritis Research UK Grant Refs: 20777, 20194 Disclosure of Interest: None declared